2022
DOI: 10.1093/schbul/sbab153
|View full text |Cite|
|
Sign up to set email alerts
|

Anandamide Hydrolysis Inhibition Reverses the Long-Term Behavioral and Gene Expression Alterations Induced by MK-801 in Male Rats: Differential CB1 and CB2 Receptor-Mediated Effects

Abstract: NMDA receptor blockade in rodents is commonly used to induce schizophrenia-like behavioral abnormalities, including cognitive deficits and social dysfunction. Aberrant glutamate and GABA transmission, particularly in adolescence, is implicated in these behavioral abnormalities. The endocannabinoid system modulates glutamate and GABA transmission, but the impact of endocannabinoid modulation on cognitive and social dysfunction is unclear. Here, we asked whether late-adolescence administration of the anandamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…In a previous study, we showed that when administered chronically in adolescence, NMDAr blockade in rats leads to recognition memory impairments and social interaction deficits in the adult animal. In parallel, we observed changes in the expression of glutamate and GABA markers, suggesting a dysregulated E/I balance (Bauminger, Zaidan, Akirav, & Gaisler-Salomon, 2022). Despite the centrality of adolescence for maturation of the E/I balance and relevance for cognitive and social functions, less attention has focused on examining the long-term impact of chronic NMDAr blockade on excitatory and inhibitory transmission in mPFC.…”
Section: Introductionmentioning
confidence: 79%
“…In a previous study, we showed that when administered chronically in adolescence, NMDAr blockade in rats leads to recognition memory impairments and social interaction deficits in the adult animal. In parallel, we observed changes in the expression of glutamate and GABA markers, suggesting a dysregulated E/I balance (Bauminger, Zaidan, Akirav, & Gaisler-Salomon, 2022). Despite the centrality of adolescence for maturation of the E/I balance and relevance for cognitive and social functions, less attention has focused on examining the long-term impact of chronic NMDAr blockade on excitatory and inhibitory transmission in mPFC.…”
Section: Introductionmentioning
confidence: 79%
“…If the non-reinforced arm was chosen, the rat was retrained on the discrimination of the previous day and tested again 24 h later. If the reinforced arm was chosen, the rat was trained on the reversal of that discrimination, i.e., the platform was moved to the opposite arm [ 41 ]. In both phases, the number of correct trials was recorded until the rat reached five consecutive correct trials.…”
Section: Methodsmentioning
confidence: 99%
“…The movements of the rat were recorded and analyzed for 15 min using a video tracking system (Ethovision × T 14.0, Noldus Information Technology) to measure locomotion (measured as distance moved in cm). Time spent in the center (s) in the first 5 min was used as a measure of anxiety-like behavior (Bauminger et al, 2022).…”
Section: Activity and Anxiety-like Behavior In An Open Field Test (Of)mentioning
confidence: 99%